Animal source foods and human nutrition - Baltenweck, Isabelle; Grace, Delia; Thorne-Lyman, A.L.; Domínguez Salas, Paula (International Livestock Research Institute, 2015)
By Isabelle Baltenweck, Delia Grace, Andrew Thorne-Lyman and Paula Dominguez-Salas to the CGIAR Research Program on Livestock and Fish review and planning meeting, 23-26 March 2015